SUBORDINASI MAKNA ANTARA AMELIORASI DENGAN PEYORASI DALAM TEKS FLYER - Zulfatun Anisah (Fakultas Syariah dan Adab Universitas Nahdlatul Ulama Sunan Giri, 2022)
The meaning of a word depends on the user of the language itself. Inknown words there are words that have a higher value and a lower value. Theexistence of this unequal meaning is known as subordinate. Words that increase invalue are called amelioration, while words that decrease in value are calledpejorations. I found this amelioration and preference in a flier, which reads “aman's success in a career must have a woman behind him, namely his partner. Andthe destruction of a man must also have a woman behind him, namely his mistress.There are inaccuracies in the use and placement of words. The words that thewriter highlights are the words male and female as amelioration, and the wordsmale, female as peyorasi. In analyzing the researchers used a conceptual approach,because there was a change in the concept, and the technique used was a dressingtechnique. Through the technique of replacing the replaced element, it is always anelement that is the main concern in the analysis. So that the results of improving theflier sentence become